Targeting of the Tec Kinase ITK Drives Resolution of T Cell–Mediated Colitis and Emerges as Potential Therapeutic Option in Ulcerative Colitis - Lechner-Grimm, Kristina; Mott, Stefanie; Al-Saifi, Ragheed; Knipfer, Lisa; Wirtz, Stefan; Atreya, Raja; Vieth, Michael; Rath, Timo; Fraass, Tina; Winter, Zoltan; August, Avery; Luban, Jeremy; et al. (Gastroenterology, 2021)
Background & Aims: The molecular checkpoints driving T cell activation and cytokine responses in ulcerative colitis (UC) are incompletely understood. Here, we studied the Tec kinase ITK in UC. Methods: We analyzed patients with inflammatory bowel disease (n = 223) and evaluated ITK activity as well as the functional effects of cyclosporine-A (CsA). In addition, 3 independent murine colitis models were used to investigate the functional role of ITK. Finally, the activity of ITK was blocked via pharmacological inhibitors and genetically engineered mice. Readout parameters were mini-endoscopy, histopathology, mucosal T cell apoptosis, and cytokine production. Results: We found an expansion of pITK-expressing mucosal CD4+ T cells in UC rather than Crohn's disease that correlated with disease severity. CsA suppressed activation of ITK in cultured CD4+ T cells and calcineurin-containing microclusters adjacent to the T cell receptor signaling complex. Functionally, the capacity of CsA to suppress activity of experimental colitis was critically dependent on ITK. Genetic inactivation of Itk via gene targeting or induction of allele-sensitive Itk mutants prevented experimental colitis in 3 colitis models, and treatment with pharmacological ITK blockers suppressed established colitis. In addition, ITK controlled apoptosis and activation of mucosal Th2 and Th17 lymphocytes via NFATc2 signaling pathways. Conclusions: ITK activation was detected in UC and could be down-regulated in cultured T cells by CsA administration. Selective targeting of ITK emerges as an attractive approach for treatment of chronic intestinal inflammation and potentially UC by driving resolution of mucosal inflammation.
CRIS-Team Scopus Importer:2021-09-24
Keywords: Cyclosporine A; Cytokines; IBD; ITK; Therapeutic Strategies